PENERAPAN TEORI HIERARKI KEBUTUHAN MASLOW DALAM PEMBELAJARAN DARING - I Wayan Rudiarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This study aims to provide an analysis of the application of Maslow's hierarchy of needs theory in online learning. This study uses a qualitative approach with data collection techniques in the form of a literature study. Based on the results of the analysis, it was found that the application of Maslow's hierarchy of needs theory can provide solutions to various obstacles found in the practice of online learning. The fulfillment of physiological needs, the need for security, the need for love and affection, the need for self-esteem, and the need for self-actualization will give students the confidence to keep their motivation in learning. Maintaining motivation which is the driving energy in learning provides space for teachers to be able to carry out learning according to planning so that learning outcomes become more optimal. Through this study, it is hoped that a positive paradigm will begin to build that online learning can be carried out effectively and efficiently so that it can be an option in the implementation of learning not only during the Covid-19 pandemic. Keywords: online learning, learning, motivation, Maslow's theory.